PERBANDINGAN THERAPY AKUPRESURE DAN NAFAS DALAM MENGURANGI NYERI PERSALINAN DI (PMB) MURSALINA TAHUN 2023 - Pane, Herviza Wulandary; Joharmi, Joharmi; Christiani, Meity (Universitas Aufa Royhan, 2023)
Labor pain is the main problem experienced by mothers giving birth. One method of reducing pain without medication that can be given continuously, is cost effective and has low risk is acupressure therapy and deep breathing relaxation. The aim of this research is to determine the comparison of acupersure therapy and breathing relaxation in reducing labor pain.This research is a type of Quasy Experimental research with a Two Group Pretest-Posttest Design. The population in this study was 30 mothers in the first stage of labor who experienced labor pain. Data collection uses observation sheets. Data analysis used the t test. The research results showed that there was a comparison of the average pain scale between the acupressure therapy group and deep breathing relaxation in reducing labor pain in mothers in the first stage of labor. The average pain scale in the acupressure therapy group was 3.07. Meanwhile, the average pain scale in the deep breathing relaxation group was 4.40. There was an average difference of 1.33 points. The results of the t-test statistical test between the acupressure therapy and deep breathing relaxation groups showed a value of p = 0.033 (p < 0.05), which means Ha was accepted. So the results of the analysis stated that there was a significant comparison between the acupressure therapy and breathing relaxation groups in reducing labor pain in mothers in the first stage of labor at (PMB) mursalina in 2023. The conclusion of this research is that acupressure therapy is more effective in reducing labor pain compared to deep breathing techniques.